2015
DOI: 10.1186/s13075-015-0610-9
|View full text |Cite
|
Sign up to set email alerts
|

Gout and risk of chronic kidney disease and nephrolithiasis: meta-analysis of observational studies

Abstract: IntroductionTo determine the prevalence of chronic kidney disease and nephrolithiasis in people with gout, and the association between gout and prevalent or incident chronic kidney disease and nephrolithiasis.MethodsSystematic review and meta-analysis of epidemiological studies. Data sources; MEDLINE, EMBASE and CINAHL databases, hand-searched reference lists, citation history and contact with authors. Eligibility criteria: cohort, case–control or cross-sectional studies which examined the occurrence of chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
115
4
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(140 citation statements)
references
References 58 publications
(218 reference statements)
1
115
4
6
Order By: Relevance
“…A recent case-control study found that stone formers who used allopurinol (potentially a surrogate for hyperuricemia) were at high risk of CKD (38). Gout is a risk factor for both CKD and nephrolithiasis (39,40). In this study, there was a significant association between higher plasma uric acid and incident CKD; however, the interaction of uric acid and stone history with CKD was not in the hypothesized direction.…”
Section: Discussioncontrasting
confidence: 49%
“…A recent case-control study found that stone formers who used allopurinol (potentially a surrogate for hyperuricemia) were at high risk of CKD (38). Gout is a risk factor for both CKD and nephrolithiasis (39,40). In this study, there was a significant association between higher plasma uric acid and incident CKD; however, the interaction of uric acid and stone history with CKD was not in the hypothesized direction.…”
Section: Discussioncontrasting
confidence: 49%
“…Під-твердженням цього стали висновки дослідження SHEP: застосування терапевтичних доз діуретиків призводить до безсимптомного підвищення рівня сечової кислоти в асоціації зі значним збільшенням кількості кардіоваскулярних подій -на 42 % у по-ловини хворих протягом року. Гіперурикемія також розглядається як важливий компонент метаболіч-ного синдрому, і безсимптомна гіперурикемія віді-грає значну роль у розвитку нефролітіазу у хворих із метаболічним синдромом [3,17].…”
Section: вступunclassified
“…Під-твердженням цього стали висновки дослідження SHEP: застосування терапевтичних доз діуретиків призводить до безсимптомного підвищення рівня сечової кислоти в асоціації зі значним збільшенням кількості кардіоваскулярних подій -на 42 % у по-ловини хворих протягом року. Гіперурикемія також розглядається як важливий компонент метаболіч-ного синдрому, і безсимптомна гіперурикемія віді-грає значну роль у розвитку нефролітіазу у хворих із метаболічним синдромом [3,17].Гіперурикемія, як компонент метаболічного синдрому, у пацієнтів є предиктором кардіоваску-лярної смертності, розвитку цукрового діабету (ЦД), АГ та нефролітіазу [6]. Підвищення рівня сечової кислоти також є незалежним чинником ризику роз-витку субклінічного коронарного атеросклерозу, а в пацієнтів з АГ, найбільш імовірно, відображає по- 616.61-008.64 DOI: 10.22141/2307616.61-008.64 DOI: 10.22141/ -1257616.61-008.64 DOI: 10.22141/ .6.2.2017 Тронько М.Д.…”
unclassified
“…Chronic hyperuricemia and gout are associated with comorbidities such as hypertension, cardiovascular disease and chronic kidney disease (CKD) [6,9,10]. Emerging evidence suggests that urate-lowering treatment (ULT) may improve these conditions [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%